Letters and autobiographical writings - Mills, C. Wright (Charles Wright) 1916-1962 (University of California Press, 2000)
One of the leading public intellectuals of twentieth-century America and a pioneering and brilliant social scientist, C. Wright Mills left a legacy of interdisciplinary and hard-hitting work, including two books that changed the way many people viewed their lives and the structure of power in the United States: White Collar (1951) and The Power Elite (1956). Mills persistently challenged the status quo within his profession - as in The Sociological Imagination (1959) - and within his country, until his untimely death in 1962. This collection of letters and writings, edited by his daughters, allows readers to see behind Mills's public persona for the first time." "This volume charts his journey from Waco, Texas, to New York City and his professorship at Columbia College, from political discussions in Greenwich Village to interviews with intellectual dissidents in Eastern Europe and the newly empowered revolutionaries in Cuba." "Mills's letters to prominent figures - including Saul Alinsky, Daniel Bell, Lewis Coser, Carlos Fuentes, Hans Gerth, Irving Howe, Dwight Macdonald, Robert K. Merton, Ralph Miliband, William Miller, David Riesman, and Harvey Swados - are joined by his letters to family members, letter-essays to an imaginary friend in Russia, personal narratives by his daughters, and annotations drawing on published and unpublished material, including the FBI file on Mills.